Developmental Trajectories of the Children of the Incarcerated: From an Educational Psychological Perspective - Arrastia, Meagan C (2015)
In the state of Georgia, more than 28,000 children have parents that are currently incarcerated (The Sentencing Project, 2013). At the nationwide-level, a total of 10 million children have at some point lived without one or both parents due to incarceration (Pew, 2010). Although the captive audience of the imprisoned parents have been studied in the past, these parents rarely have an understanding of their children’s experiences. In fact, a majority of the state prison population reported never getting to see their children for visitation (Glaze & Maruscak, 2010). Recent research has found high rates of learning disabilities, communication problems, and developmental delays among these children (Turney, 2014). In order to understand the supports and barriers to success for this population, longitudinal educational research must be conducted. In this paper, I review the existing literature on the children of the incarcerated and highlight areas in which educational psychology research could illuminate the developmental trajectories of this population. Areas for future research, include the effects of which parent is in prison, other role models, peer groups, environmental factors, and intervention programs. Such research could better focus future resources for targeted early intervention to promote high school graduation and prosocial behavior